Singlebatch lot streaming in a twostage assembly system. (3rd January 2012) - Sarin, Subhash C.; Yao, Liming; Trietsch, Dan
We address a singlebatch lot streaming problem for a twostage assembly system. The first stage consists of m parallel subassembly machines, each devoted to a component type. A single assembly machine at the second stage assembles a unit of a product after all m components (one each from the subassembly machines) are ready. The batch consists of U units. Detached or attached setups are necessary before the start of the first item on each machine. Given a fixed maximal number of sublots, the problem is to determine integer sublot sizes to minimise the makespan. We present a polynomialtime algorithm to obtain an optimal solution.